2009
DOI: 10.1007/s12072-009-9136-z
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with chest tube insertion for hepatic hydrothorax

Abstract: Purpose Case reports and small case series have reported a high rate of complications associated with chest tube placement for hepatic hydrothorax. We describe the inhospital and 3-month outcomes of patients who have had this procedure. Methods A retrospective medical record review was performed of all patients admitted to a tertiary care center over a 10-year period with a chest tube placed for hepatic hydrothorax. Demographic data and outcomes were collected and analyzed. Results Seventeen patients were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 26 publications
(32 reference statements)
2
67
1
4
Order By: Relevance
“…Pleurodesis and peritoneovenous shunts are surgical options that are usually associated with rapid fluid reaccumulation and procedure-related complications, and they are not generally recommended as treatments for HH [14,15] . In the absence of a large pneumothorax, hemothorax, or frank empyema, a chest tube should not be inserted in patients with HH [16,17] . Up to 25% of patients with HH will become refractory to treatment [18] , compared to only 10% [17] of patients with cirrhotic ascites.…”
Section: Introductionmentioning
confidence: 99%
“…Pleurodesis and peritoneovenous shunts are surgical options that are usually associated with rapid fluid reaccumulation and procedure-related complications, and they are not generally recommended as treatments for HH [14,15] . In the absence of a large pneumothorax, hemothorax, or frank empyema, a chest tube should not be inserted in patients with HH [16,17] . Up to 25% of patients with HH will become refractory to treatment [18] , compared to only 10% [17] of patients with cirrhotic ascites.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that this serious complication may follow chest tube placement in such patients in 29% of cases [6] . Although surgical decortication is indicated for the treatment of trapped lung [8] , major surgery of any kind, and decortication in particular, carries a high risk of peri-operative complications and death in decompensated cirrhotic patients [8,9] .…”
Section: Discussionmentioning
confidence: 90%
“…TIPS has been demonstrated to be effective in controlling hepatic hydrothorax refractory to medical management [5] . Placement of percutaneous drainage catheters is associated with a high risk of various complications, including secondary bacterial pleuritic/ empyema [6,7] and current practice guidelines published by the American Association for the Study of Liver Diseases (AASLD) consider chest tube placement contra-indicated for the purpose of managing hepatic hydrothorax [3] .…”
Section: Discussionmentioning
confidence: 99%
“…The condition is classically managed with salt restriction, diuretics and pleurocentesis in the presence of overt symptoms. Chest drain placement for HH caries significant morbidity and mortality [3]. Placement of large bore subcutaneous drains and increasing catheter suction has been shown to improve SCE drastically, [4] even though former modality has not been studied in cirrhotics.…”
mentioning
confidence: 99%